Analysis of the Influence of Destination Image, Tourist Attractiveness and Experience of Climbers on Interest in Repeat Visits with Satisfaction as an Intervening Variable - Nurcholis Nurcholis (PT. Publikasiku Academic Solution, 2023)
The purpose of this study was to identify and analyze the influence of destination image, tourist attraction, and experience of climbers on intention to return with satisfaction as an intervention variable for climbers of Mount Gede Pangrango. Instruments used in this research were questionnaires to 150 respondents with descriptive and quantitative data processing and analysis. Descriptive analysis in the research aims at describing the characteristics of the respondents and describing the research variables, while quantitative analysis is carried out using SEM - PLS (Partial Least Square) tools with the aim of testing the hypothesis. Based on the results of the analysis in this study, it can be explained that the image of the destination, tourist attraction, and experience of climbers has a positive and significant effect on satisfaction among climbers of Mount Gede Pangrango. Destination image, tourist attraction, climber experience, and satisfaction have a positive and significant effect on intention to return to climbers of Mount Gede Pangrango. Travel image, tourist attraction, and climber experience have a positive and significant effect on Repeat Visit Interest with Satisfaction as an intervention variable for climbers of Mount Gede Pangrango.